2021
DOI: 10.1007/s11207-021-01934-x
|View full text |Cite|
|
Sign up to set email alerts
|

Common Origin of Quasi-Periodic Pulsations in Microwave and Decimetric Solar Radio Bursts

Abstract: How to cite:Please refer to published version for the most recent bibliographic citation information.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The phenomenon of quasi-periodic bursts can be attributed to many physical processes like periodic reconnections, loop oscillations, etc. (Nakariakov & Melnikov 2009;Kashapova et al 2021). In meter waves, several quasi-periodic oscillations during type-I (Mohan 2021b; Mondal & Oberoi 2021) and type-III bursts (Mohan et al 2019) have been reported.…”
Section: Quasi-periodic Burstsmentioning
confidence: 99%
“…The phenomenon of quasi-periodic bursts can be attributed to many physical processes like periodic reconnections, loop oscillations, etc. (Nakariakov & Melnikov 2009;Kashapova et al 2021). In meter waves, several quasi-periodic oscillations during type-I (Mohan 2021b; Mondal & Oberoi 2021) and type-III bursts (Mohan et al 2019) have been reported.…”
Section: Quasi-periodic Burstsmentioning
confidence: 99%
“…Because it is unnecessary to discuss the periodic behavior if there are only one or two peaks, which might be just a coincidence, for instance, the similar time interval between successive peaks occurred by chance (Nakariakov et al 2019;Li 2022a). The flare-related QPPs have been detected almost in the entire solar spectrum, i.e., radio/microwaves, white lights, Hα, ultraviolet/extreme ultraviolet (UV/EUV), Lyα, soft/hard X-rays (SXR/HXR), and γrays (e.g., Nakariakov et al 2010;Li et al 2020aLi et al , 2020bClarke et al 2021;Hong et al 2021;Kashapova et al 2021;Zhao et al 2021;Karlický et al 2022;Li 2022b;Shi et al 2022). The observed quasi-periods vary from subseconds to several tens of minutes (Melnikov et al 2005;Ning 2017;Hayes et al 2020;Karlický & Yasnov 2021;Zimovets et al 2021a;Howard & MacGregor 2022;Ning et al 2022;Shen et al 2022;Zhou et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…They are frequently identified as a series of repetitive but irregular pulsations with anharmonic and symmetric triangular shapes, referring to non-stationary QPPs (e.g., Nakariakov et al, 2019). The observation of QPPs has been reported in flare time series over a broad range of wavelengths, ranging from radio/microwave emissions through ultraviolet (UV) and white light wavelengths to soft and hard X-rays (SXR/HXR) channels, and even in the γ-ray emission (e.g., Nakariakov et al, 2010a;Tan et al, 2016;Milligan et al, 2017;Li et al, 2017b;Kashapova et al, 2021;Kolotkov et al, 2021;Lu et al, 2021;Doyle et al, 2022;Smith et al, 2022;Zhang et al, 2022a). Generally, a typical QPP should be at least three successive and complete pulsations.…”
Section: Introductionmentioning
confidence: 99%
“…The flare QPPs with long periods in the order of seconds and minutes, which could detect in almost all wavelengths, are frequently interpreted in terms of magnetohydrodynamic (MHD) waves in slow modes (e.g., Wang et al, 2021), kink modes (e.g., Nakariakov et al, 2021), and sausage modes (e.g., Li et al, 2020a). In such case, the flare QPPs with periods larger than 1 minute could be associated with slow sausage waves (Sadeghi and Karami, 2019;Gao et al, 2021), global kink waves (Duckenfield et al, 2019;Gao et al, 2022), and slow magnetoacoustic waves (Wang, 2011;Ofman et al, 2012;Yuan et al, 2015;Prasad et al, 2022); while those with periods in the order of seconds are often explained as fast sausage or kink waves (Inglis and Nakariakov, 2009;Guo et al, 2021;Kashapova et al, 2021), depending on whether the plasma loop can be compressible or incompressible (Yuan and Van Doorsselaere, 2016;Nakariakov and Kolotkov, 2020). Those long-period QPPs might be also associated with the repetitive magnetic reconnection (Thurgood et al, 2019;Karampelas et al, 2022).…”
Section: Introductionmentioning
confidence: 99%